PROSPECTS FOR ENTREPRENEURSHIP DEVELOPMENT IN THE REGIONS - Mahbuba Kholikova (Scholar Express Journals, 2021)
The main goal of the economic policy pursued in Uzbekistan for the development of entrepreneurship is to ensure a decent standard of living and quality of life, to take a worthy place among the developed democracies. Thus, one of the most pressing issues in our country's economy is a precise functioning of the mechanism for its implementation. This article analyses the prospects for entrepreneurship development in the regions of our country.
Keywords: Small business; world experience; enterprise; population